Cancer related cachexia management – blessing for patients and curse for the National Health Fund? A critical analysis of cachexia treatment in Poland - Krzemieniecki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2008)
Cancer anorexia/cachexia syndrome (CAC) is found in almost two thirds of all cancer patients in the course of their disease. Worse clinical status and decrease in the quality of life in this subset of patients are the most common consequences of cachexia. Nutritional disorders can be responsible for anticancer treatment discontinuation in many patients with potentially treatable disease. The modern treatment modalities for CAC syndrome and number of patients suitable for such treatment generate high reimbursement costs. Are there any strong rationales to use megestrol acetate in all cachectic patients? The most clinically accurate selection criteria for CAC syndrome therapy and its timing as well as use of other strategies improving patients’ nutrition can lead to validation of local guidelines for management of this important clinical issue.